Geert Hofstede et al's Set of National Cultural Dimensions - Popularity and Criticisms - Kiril Dimitrov (Economic Alternatives, 2014)
This article outlines different stages in development of the national culture model, created by Geert Hofstede and his affiliates. This paper reveals and synthesizes the contemporary review of the application spheres of this framework. Numerous applications of the dimensions set are used as a source of identifying significant critiques, concerning different aspects in model's operation. These critiques are classified and their underlying reasons are also outlined by means of a fishbone diagram.
Keywords: M14; Z1; 330; cultural differences; national culture; business culture; Geert Hofstede